Alleviation of masticatory disturbance with an occlusal splint in a Duchenne muscular dystrophy patient. (7th April 2021) - Fukumoto, Yutaka; Miyama, Takeshi
Abstract: Aim: To present an occlusal splint effective for alleviating masticatory disturbance in Duchenne muscular dystrophy (DMD). Case report: A 13‐year‐old male DMD patient with masticatory disturbance presented with an open bite, with occlusal contact only between the first and second molars bilaterally and reduced masticatory performance. We applied an occlusal splint that achieved occlusal contact for all teeth and monitored its effects on masticatory function over 6 years. The occlusal splint increased occlusal contact points from 11 to 60. Although occlusal force remained at 13.9‒16 kg, masticatory performance increased, and the number of mastication strokes increased from 124 to 169. Masseter muscle activity decreased from 76.8% to 33.4% maximum voluntary contraction (MVC) and digastric muscle activity increased from 8.7% to 18.0% MVC. Time from start of peanut mastication to swallowing decreased, and the vertical mastication cycle diameter and its width on the habitual side increased. Conclusions: Masticatory disturbance in a DMD patient was alleviated using an occlusal splint. The number of mastication strokes and the digastric to masseter muscle activity ratio were increased. Furthermore, the mastication cycle was enlarged, which increased masticatory movement. As masseter muscle activity during mastication decreased, the occlusal splint likely reduced muscle fatigue during masticatory movement.